A Southern Perspective on Development Studies - Mallorquin, Carlos (Ariadna Ediciones, 2020)
This book suggests the importance of examining alternative discourses in the social sciences, in this case economics, beyond western-centric cultural milieu. The account attempts to unveil the existence of a post Second World War economic approach developed in Latin America. The perspective questioned the dominant economic science disseminated within and outside the Anglo-Saxon or Eurocentric countries (western-centric academia) during the 1950´s. Today, after the appalling cataclysms in welfare and equality generated by neoclassical economics, an alternative economics seems order in the Northern and Southern hemisphere. The rebirth of Latin American Structuralism within the developing countries, and the widely publicized names of Raúl Prebisch, Celso Furtado among others, within the western-centric audiences requires an up to date of the vocabulary and concepts. Retrospectively these authors discussed can be examined as the original sources in Latin America among those who developed the basis of decolonial thought. The book problematizes the domestication of Latin American Structuralism in the Northern or Southern hemisphere alike and discusses its potential similarities to Post-Keynesian perspectives related to power asymmetries among countries, firms, and heterogenous agents.